Investigating the organizational commitment and its associated factors among the staff of the health sector: a cross-sectional research - Mahdis Paparisabet; Amir Hossein Jalalpour; Farzaneh Farahi; Zeinab Gholami; Fatemeh Shaygani; Neda Jalili; Sama Rashid Beigi; Milad Ahmadi Marzaleh; Hadis Dastgerdizad Elyaderani (BMC, 2024)
Abstract Introduction Organizational commitment (OC) significantly impacts the quality of care provided by healthcare staff. It reflects employees' connection to and engagement with their organization, affecting job satisfaction, employee turnover, and the overall success of the healthcare organization. This research seeks to assess OC levels and identify its influencing factors among health sector staff in Shiraz, southwestern Iran. Methods In this cross-sectional study, the staff of the health sector including physicians/family physician (FP), midwives, healthcare workers, psychologists, dentists, and nutritionists were selected through a multi-stage sampling; they filled out an online 36-item questionnaire (12 demographic items and 24-item Allen and Mayer OC questionnaire). The data were analyzed using SPSS software (version 25). Descriptive statistics of OC scores were provided. Also, independent samples t-test and analysis of variance were used as statistical tests, and P-value < 0.05 was considered the significant level. Results Overall, 289 staff with a mean age of 32 ± 7.6 years participated in this study. The OC total mean score was higher in the public sector compared with the private sector and higher in the non-FP team compared with the FP team. The mean score of all types of OC among all job positions was low. Moreover, education level, workplace, job experience in current job, engagement in other jobs for making money, and FP staff showed a significant association with the total mean score of OC. Conclusion According to the results, OC among health sector staff is low. Therefore, policymakers in the health sector are strongly recommended to implement immediate measures to enhance this critical factor among their workforce.